THE INFLUENCE OF PERCEIVED USEFULNESS, EASE OF USE, TRUST, AND RISK TOWARDS GOJEK ACTUAL USAGE WITH BEHAVIORAL INTENTION TO USE AS INTERVENING VARIABEL - ALIFIARDI, ARRIZKY AZHAR (Jurnal Ilmiah Mahasiswa FEB, 2019)
The purpose of this study is to explain and to predict the influence of perceived usefulness, ease of use, risk, and trust in behavioral intentions to use and behavioral intentions to use against the actual use of GO-JEK applications. This type of research is quantitative explanatory research and data is collected using survey methods, namely questionnaires. Respondents in this study were 581 active students in the accounting department of the Faculty of Economics and Business, Brawijaya University 2015 and 2016. Academic data and hypothesis data were analyzed using structural equation models (SEM) based on Partial Least Squares (PLS). The results showed that the behavioral intention to use GOJEK was influenced significantly and positively by perceived usefulness, perceived ease of use, perception of trust, and perceived risk. So that it can be concluded that the higher the perceived usefulness, perceived ease of use, perception of trust, and perceived risk, the higher the behavioral intention to use GOJEK. This study also shows that GOJEK's actual use is significantly and positively influenced by the behavioral intention to use GOJEK. It can be concluded that the higher the behavioral intention to use GOJEK, the higher the actual use of GOJEK applications.Keywords: Perceived of Usefulness, Perceived Ease of Use, Perceived of Risk, Perceived of Trust, Behavior Intention to Use, Actual Usage, Go-Jek